The making of the tabernacle and the construction of priestly hegemony - MacDonald, Nathan 1975- (Oxford Oxford University Press, 2023)
How did the Jerusalem high priests go from being cultic servants in the sixth century BCE to assuming political supremacy at some point during the third or second century? This book examines how the conditions were created for the priesthood's rise to power by examining the tabernacle accounts found in Exodus and Leviticus.
Also issued in print: 2023. - Includes bibliographical references and index. - Description based on online resource and publisher information; title from PDF title page (viewed on August 21, 2023)
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Priests, Jewish -- History; Judaism -- History; Priests, Jewish -- Jerusalem -- History; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Tabernacle; Priester; Geschichte; Exegese; Judentum; Religion; Religion & beliefs; Jerusalem -- Church history